An improved folate stable isotope dilution assay of unexploited food sources from Brazil - Obermaier, Lisa; da Mata, Barbara Paes Miglioli; Perego, Caio Humberto; Sivieri, Kátia; Salgaço, Mateus Kawata; dos Santos, André Gonzaga; Boehni, Ruth; Groehn, Viola; Knapp, Jean-Pierre; Rychlik, Michael (Frontiers in Nutrition, 2023)
Brazil has a diverse plant community, including underutilized non-conventional food crops (PANCs), which have the potential to be a rich source of food and contribute to food security. For assessing the folate content in a range of Brazilian PANCs, we extended the validation of an existing stable isotope dilution assay (SIDA) for the stably 13C-labelled 10-formyl-Pte[13C5]Glu (10-CHO-Pte[13C5]Glu)). The SIDA method with an enzymatic treatment, purification step, and an LC-MS/MS measurement was validated regarding linearity, precision, LoD/LoQ, and recovery for 10-CHO-PteGlu. After successful validation, the study of some underutilized Brazilian non-conventional fruits and leaves from the São Paulo State University campus revealed them as an important source of folates. It provided the first insights into the folate content of unexploited food sources from Brazil. Pequi had the highest folate content among the fruits studied, with mean values of 333 µg/100 g based on fresh weight (FW). The analysis also shows that different cultivars of fruit or fruits from different growing locations have a high variability in folate content or other nutritional factors. In most fruits, the main vitamer was 5-CH3-H4folate, but jenipapo and taioba showed the highest content of 10-CHO-PteGlu with 28.22 µg/100 g (FW) in jenipapo peel and 75.64 µg/100 g (FW) in the taioba leaves. Thus, this study also provides results on the importance of the folate vitamer 10-CHO-PteGlu contributing to the total folate content.